2006
DOI: 10.1266/ggs.81.381
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the domain structure in FlgJ, a bacterial protein involved in flagellar rod formation

Abstract: Bacterial flagellar rod structure is built across the peptidoglycan (PG) layer. A Salmonella enterica flagellar protein FlgJ is believed to consist of two functional domains, the N-terminal half acting as a scaffold or cap essential for rod assembly and the C-terminal half acting as a PG hydrolase (PGase) that makes a hole in the PG layer to facilitate rod penetration. In this study, molecular data analyses were conducted on FlgJ data sets sampled from a variety of bacterial species, and three types of FlgJ ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…As such, a sensitive method to assay for the presence of extracellular FlgJ was needed. To that end, the influenza virus-derived hemagglutinin (HA) tag was inserted into the chromosomal flgJ gene in the linker region between the N-and C-terminal domains believed to be unstructured (31). The resulting FlgJ-3ϫHA chimera (TH17693) exhibited wildtype motility and allowed for sensitive and unambiguous identification of FlgJ, expressed from its native, chromosomal locus, by standard Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As such, a sensitive method to assay for the presence of extracellular FlgJ was needed. To that end, the influenza virus-derived hemagglutinin (HA) tag was inserted into the chromosomal flgJ gene in the linker region between the N-and C-terminal domains believed to be unstructured (31). The resulting FlgJ-3ϫHA chimera (TH17693) exhibited wildtype motility and allowed for sensitive and unambiguous identification of FlgJ, expressed from its native, chromosomal locus, by standard Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Nambu et al (37) found that various alphaproteobacteria, including R. sphaeroides, possess proteins homologous to FlgJ that lack the lytic transglycosylase domain, whereas beta-and gammaproteobacteria possess FlgJ that contains the N-terminal domain fused to the lytic C-terminal moiety. It should be noted that this catalytic domain does not show muramidase enzymatic activity (21).…”
Section: Fig 5 Affinity Blot and Coimmunoprecipitation (A)mentioning
confidence: 99%
“…Similar to FlgJ Bb , the FlgJ homologs in other sequenced spirochetes also belong to the family of singledomain FlgJ; they all lack the C-terminal PGase domain, suggesting that the spirochetes may have evolved another route to process the passage of elongating rods through the PG layer. It has been postulated that the class of dual-domain FlgJ proteins has evolved by merging two individual domains together (44). Consistent with this assumption, the absent PGase domain has been identified in the genome of R. sphaeroides, which is encoded by an independent gene (14).…”
Section: Figmentioning
confidence: 83%
“…FlgJ homologs are present in many bacteria (44). However, their functions in flagellation and motility have only been studied in S. Typhimurium and Rhodobacter sphaeroides (14,24,25,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation